APPLICATION OF HIGHER MATHEMATICS TO CHEMISTRY: MODELING REACTION RATE USING DIFFERENTIAL EQUATIONS - Urinboyeva L. U.; Mirxaitov B. G. (Modern American Journals, 2025)
The article examines the application of higher mathematics to practical, in particular chemical processes, how to model the rate of a chemical reaction using differential equations, and reveals their meaning.
Keywords: Chemistry, chemical processes, chemical reaction rate, differential equations, modeling, integral, logarithm.